PENERAPAN MODEL SQ4R PADA MATERI MOMENTUM DAN IMPULS UNTUK MENINGKATKAN KEMANDIRIAN BELAJAR SISWA KELAS X SMA NEGERI 8 PEKANBARU - Mifta Rahmadiyah; Mitri Irianti; Zulirfan ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to describe the self directed learning of students in physics through the application of SQ4R model on the momentum and impulse subject. This type of research is pre-experiment research using one group pre-test post-test design. The participants are the students of X10 class SMAN 8 Pekanbaru with the number of 27 people. The pre-exeriment research instrument use self directed learning ability questionnaires. Descriptive analysis technique is used as data analysis technique. The results showed that the initial level of self directed learning ability of the students was at score 2.88 and after application of SQ4R model was at score 2.69. This study concludes that the SQ4R model does not increase the independence of physics learning on the momentum and impulse subject.Keywords: SQ4R, Self Directed Learning Ability, Momentum and Impulse